2010
DOI: 10.1103/physrevb.82.201403
|View full text |Cite
|
Sign up to set email alerts
|

Stopping of energetic argon cluster ions in graphite: Role of cluster momentum and charge

Abstract: We show that the implantation depth for argon clusters in graphite scales linearly with cluster momentum. A plot of implantation depth versus the momentum scaled with the projected surface area of the cluster falls on the same universal plot as that shown for semiconductor and metallic clusters, thus providing a universal scaling law for cluster implantation. Molecular dynamics simulations provide some insight to the mechanisms behind the empirical observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…3 However, recent experiments of cluster implantation supported by molecular dynamics (MD) simulations demonstrated that a universal dependence of the cluster stopping can be reached at least for graphite. 12,13 It was proved that R p can be linearly scaled with the square root of cluster kinetic energy E kin , which is proportional to cluster momentum.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…3 However, recent experiments of cluster implantation supported by molecular dynamics (MD) simulations demonstrated that a universal dependence of the cluster stopping can be reached at least for graphite. 12,13 It was proved that R p can be linearly scaled with the square root of cluster kinetic energy E kin , which is proportional to cluster momentum.…”
mentioning
confidence: 99%
“…The higher level of amorphization of these samples compared to the ones implanted by the lower-energy clusters (4 and 9 keV) leads to the situation where the amorphous carbon can be etched just by the thermal annealing, similar to the case of cluster-implanted graphite. 12,13 At elevated temperatures, carbon atoms undergo chemical reactions with oxygen, yielding volatile compounds. Thus, the triangular pits on the samples implanted with energies of 12 and 15 keV appear directly after the annealing.…”
mentioning
confidence: 99%
See 3 more Smart Citations